KUALITAS PELAYANAN PUBLIK DALAM MEKANISME PELAYANAN KARTU KELUARGA DI KECAMATAN PURWOSARI KABUPATEN PASURUAN - Aminullah Aminullah; Israyati Rifqoh (Journal Publicuho, 2021)
Public service is the State's effort to fulfill the basic needs of every citizen's civil rights for goods, services or services. The purpose of this study is to determine the quality of service for making family cards in Purwosari sub-district. promise and on time, responsive or alertness of officers in helping to serve and handle community complaints in obtaining information. The research method used in this research is qualitative research with descriptive analysis methods with primary data collection techniques carried out by interviewing by asking questions from the community service users in the sub-district purwosari, with the help of data obtained by literature study and field observations